Controllable fabrication of Li-rich layered oxide Li1.2Mn0.54Ni0.13Co0.13O2 microspheres for enhanced electrochemical performance. Issue 28 (5th July 2021) - Gao, Zhi; Hu, Shengyue; Pan, Xiaoliang; Liu, Lijun; Xie, Shikun; Xie, Chengning; Yuan, Huiling
Abstract : Li1.2 Mn0.54 Ni0.13 Co0.13 O2 microspheres assembled by nanoplates are prepared by a co-precipitation and calcination method using metal oxalate microspheres as a template, exhibiting improved electrochemical properties compared to the nanoplates. Abstract : Li-Rich layered oxide microspheres are considered as one of the most attractive architectures for energy storage in batteries due to their high tapped densities and good cycling stabilities. However, the synthesis of Li-rich layered oxide microspheres derived from metal oxalate microspheres as a template still remains a challenge. Here, Li1.2 Mn0.54 Ni0.13 Co0.13 O2 microspheres assembled by orthogonally arranged nanoplates are synthesized by a simple co-precipitation method followed by a calcination process using metal oxalate microspheres as the template. The amount of H2 C2 O4 ·2H2 O in the co-precipitation reaction is found to distinctly affect the final structure of the products. When used as a cathode material for lithium ion batteries, the microspheres achieve a discharge capacity of 228 mA h g −1 at 0.5C with a capacity retention of 87% after 100 cycles. These results can originate from the porous structure of the microspheres, which may not only ensure fast electrolyte accessibility and enlarge the exposed surface area, but also enhance the structural stability.